2024
DOI: 10.1039/d3tb01844j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in vivo antiviral activity against pseudorabies virus through transforming gallic acid into graphene quantum dots with stimulation of interferon-related immune responses

Shiyi Ye,
Fei Su,
Junxing Li
et al.

Abstract: With the urgent need of antiviral agents, antiviral materials with high biocompatibility and antiviral effects have attracted numerous attentions. In this study, gallic acid, a nature polyphenolic compound, was transformed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…Raghavan et al evaluated the potential of GQDs as neurotrophic agents and found the upregulation of neurotrophic factors in GQDs treating mouse neuroblastoma cells [290]. Ye et al reported that gallic acid derived GQDs showed antiviral activity against pseudorabies virus and regulated the expression of interferon-related antiviral proteins in vero cells [291].…”
Section: Therapeutic Agentsmentioning
confidence: 99%
“…Raghavan et al evaluated the potential of GQDs as neurotrophic agents and found the upregulation of neurotrophic factors in GQDs treating mouse neuroblastoma cells [290]. Ye et al reported that gallic acid derived GQDs showed antiviral activity against pseudorabies virus and regulated the expression of interferon-related antiviral proteins in vero cells [291].…”
Section: Therapeutic Agentsmentioning
confidence: 99%